2020
DOI: 10.1177/0886260520957693
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Trauma and Sexual Function and Satisfaction: The Mediating Role of Negative Affect Among Survivors of Military Sexual Trauma

Abstract: Healthy sexual function among women service members/veterans (SM/Vs) is associated with higher quality of life, lower incidence and severity of mental health diagnoses, higher relationship satisfaction, and less frequent suicidal ideation. Although trauma exposure has been established as a predictor of poor sexual function and satisfaction in women SM/Vs, no study to date has examined whether specific trauma types, such as military sexual trauma (MST), increase risk for sexual issues. Moreover, the possible me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…MST is associated with more severe PTSD and mental health symptoms when compared with other trauma types (Blais et al, 2022;Sexton et al, 2017). While several non-controlled, mixed-gender studies conducted in intensive outpatient or residential PTSD rehabilitation programs found no association between MST and treatment outcome after accounting for pretreatment differences in severity (Christ et al, 2022;Holliday et al, 2020;Rauch et al, 2021;Tiet et al, 2015;Voelkel et al, 2015), some studies have found persistent differences in treatment response as a function of whether MST was the index trauma (Zalta et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…MST is associated with more severe PTSD and mental health symptoms when compared with other trauma types (Blais et al, 2022;Sexton et al, 2017). While several non-controlled, mixed-gender studies conducted in intensive outpatient or residential PTSD rehabilitation programs found no association between MST and treatment outcome after accounting for pretreatment differences in severity (Christ et al, 2022;Holliday et al, 2020;Rauch et al, 2021;Tiet et al, 2015;Voelkel et al, 2015), some studies have found persistent differences in treatment response as a function of whether MST was the index trauma (Zalta et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies on MSA have either been restricted to women samples (e.g., Blais, 2020; Blais et al, 2020, 2022; Creech & Orchowski, 2016) or had a small sample of men with MSA (e.g., Tannahill et al, 2021). By having a larger sample of men with a history of MSA, the current study was able to test whether the relationships between revictimization experiences, PTC, and PTSS varied by gender.…”
Section: Discussionmentioning
confidence: 99%
“…PTSD and posttraumatic stress symptoms (PTSS) are associated with lower quality of life (Vogt et al, 2017), sexual dysfunction (Blais et al, 2022), poorer interpersonal functioning (Blais, 2020, 2022; Blais & Zalta, 2023), substance misuse (Schumm & Chard, 2012), and suicidal ideation and attempts (Wisco et al, 2014), highlighting the importance of continuing to study risk factors of PTSS to fine-tune assessments and treatments. Traumas that involve sexual violation are associated with the highest risk for PTSS (Blais et al, 2020; Wisco et al, 2014), with repeated exposure conferring even greater risk (see review, Classen et al, 2005; Tirone, Bagley et al, 2020a). Notably, those with a history of military sexual assault (MSA), or sexual assault that occurred during their military service, are 2 to 4.5 times more likely to have experienced previous sexual assault compared to those without a history of MSA (Schry et al, 2015, 2016), and is significantly associated with greater risk for sexual revictimization (see review, Tirone, Bagley et al, 2020a).…”
mentioning
confidence: 99%
“…Indeed, experiencing MSV is associated with increased risk for posttraumatic stress disorder (PTSD), depression, substance and alcohol use disorders, as well as suicide (e.g., Blais & Geiser, 2019;Kimerling et al, 2007). Moreover, MSV is positively correlated with greater distress relative to other trauma exposures, including combat (i.e., Blais et al, 2020;Blais & Monteith, 2019). In fact, MSV is associated with more severe distress and impairment relative to sexual violence that occurred before or after military service (Creech & Orchowski, 2016;Himmelfarb et al, 2006), highlighting its complex and lasting nature.…”
mentioning
confidence: 99%